2002
DOI: 10.1046/j.1442-2042.2002.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical stress between laparoscopy and open surgery in the field of urology by measurement of humoral mediators

Abstract: Background: Recently, laparoscopic procedures have become more common in urological surgery, and are suggested to be less stressful compared with open surgery; however, little data on objective evaluation of surgical stress after laparoscopic surgery are available. The objective of this study was to compare surgical stress between laparoscopic and open surgery in the field of urology by measurement of humoral mediators. Methods: Blood samples were obtained from 25 patients who underwent laparoscopic surgery (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 22 publications
(24 reference statements)
2
39
0
2
Order By: Relevance
“…[7] Although its success rates are comparable to those of open surgery, it has provided the advantages of lower mortality rates, and shorter hospital stays. [8,9] Various studies have indicated the success rates of laparoscopic pyeloplasty as 88-100 percent. [10] However widespread use of laparoscopic pyeloplasty has been restricted because of its challenging technique, and longer learning-curve.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Although its success rates are comparable to those of open surgery, it has provided the advantages of lower mortality rates, and shorter hospital stays. [8,9] Various studies have indicated the success rates of laparoscopic pyeloplasty as 88-100 percent. [10] However widespread use of laparoscopic pyeloplasty has been restricted because of its challenging technique, and longer learning-curve.…”
Section: Discussionmentioning
confidence: 99%
“…14 The stress response to laparoscopic surgery as measured by catecholamines, glucocorticoids and humoral mediators is less than that with an open operation. 15 Drawbacks of laparoscopic surgery include steep learning curve, longer operating times and higher overall costs. In the last 10 years, laparoscopy has revolutionized urology, yet many laparoscopic techniques remain more difficult to perform than corresponding tasks in conventional open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study, Japanese researchers grouped several laparoscopic procedures together (laparoscopic radical prostatectomy, nephrectomy, adrenalectomy and handassisted nephrectomy) and compared them with a group of open procedures (radical prostatectomy, cystectomy and nephrectomy) [11]. The laparoscopic group had a significantly smaller increase in stress-response mediators, IL-6, IL-10 and granulocytic elastase, than the open group.…”
Section: Laparoscopic Urological Surgery and Stressmentioning
confidence: 99%